Feasibility of ionization-mediated pathway for ultraviolet-induced melanin damage - Mandal, Mukunda; Das, Tamal; Grewal, Baljinder K.; Ghosh, Debashree (Journal of Physical Chemistry B, 2015)
Melanin is the pigment found in human skin that is responsible for both photoprotection and photodamage. Recently there have been reports that greater photodamage of DNA occurs when cells containing melanin are irradiated with ultraviolet (UV) radiation, thus suggesting that the photoproducts of melanin cause DNA damage. Photoionization processes have also been implicated in the photodegradation of melanin. However, not much is known about the oxidation potential of melanin and its monomers. In this work we calculate the ionization energies of monomers, dimers, and few oligomers of eumelanin to estimate the threshold energy required for the ionization of eumelanin. We find that this threshold is within the UV-B region for eumelanin. We also look at the charge and spin distributions of the various ionized states of the monomers that are formed to understand which of the ionization channels might favor monomerization from a covalent dimer.

Facile access to a Ge(II) dication stabilized by isocyanides - Swamy, V. S. V. S. N.; Yadav, Sandeep; Pal, Shiv; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2016)
Herein, we introduce isocyanide as a ligand in main group chemistry and describe the facile isolation of a Ge(II) dication. The reaction of 2,6-dimethylphenylisocyanide with GeCl2 leads to the formation of a Ge(II) dication with two [GeCl3](-) molecules as counter anions. The dicationic Ge(II) center is bound to four isocyanide ligands and also holds a lone pair of electrons. DFT calculations reveal that the dication is stabilized only by sigma-donation from the four isocyanide ligands. Natural population analysis gives a charge of +0.74 on the Ge(II) center, indicating that the positive charge is shared by the isocyanide substituents.